WHOLESALE TRADE ENTERPRISES UNDER MARTIAL LAW CONDITIONS - VENHEROVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the functioning of wholesale trade enterprises in Ukraine under the conditions of martial law caused by the full-scale Russian invasion in 2022. The study highlights the crucial role of wholesale trade as an intermediary in the national economy, ensuring the movement of goods from producers to consumers and maintaining supply stability during the crisis. The paper analyzes the dynamics of the wholesale sector before and during the war, emphasizing the transformation of business models, logistics chains, and market behavior. Based on the data of the State Statistics Service, YouControl and Gradus Research Company, the author identifies that despite large-scale destruction and logistical disruptions, the Ukrainian wholesale trade sector has shown high adaptability.The research reveals the main challenges faced by enterprises: loss of infrastructure, relocation of warehouses, shortage of personnel due to migration and mobilization, increased transportation costs, and decreased purchasing power. At the same time, new opportunities emerged — digitalization of trade processes, the growth of e-commerce and online wholesale platforms, and strengthening cooperation between producers and distributors. The article outlines the main strategies used by enterprises to ensure business continuity: diversification of suppliers, optimization of assortment, partnership logistics, and adaptation of marketing decisions to wartime conditions.The study concludes that wholesale enterprises play a vital role in sustaining the Ukrainian economy and ensuring the country’s resilience. Despite wartime difficulties, wholesale trade remains one of the most active business sectors, accounting for a significant share of new registered enterprises and large taxpayers in 2022–2023. The author emphasizes that after the victory, this sector will become one of the drivers of post-war economic recovery, participating in reconstruction and strengthening national supply chains. The findings can serve as a basis for forming public policies and enterprise strategies aimed at enhancing the sustainability and competitiveness of the wholesale trade sector during  the war.
Keywords: wholesale trade; wholesale turnover; martial law; wholesale enterprises; business resilience